Теоретичні засади модернізаційних перетворень соціально-економічних систем - Олексюк, Віталій Олександрович; Oleksiuk, Vitaliy (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2022)
У статті здійснено аналіз теоретичних засад й елементів інституціонального забезпечення модернізації національної економіки. Теоретико-методологічним базисом дослідження є системний підхід до обґрунтування теоретичних положень й інструментів інституціонального регулювання модернізаційної динаміки. Акцентовано, що онтологічним фундаментом для реалізації модернізаційних перетворень виступають специфічні реалії перехідних соціально економічних систем, які трансформуються у більш досконалу модель розвитку. Аргументовано, що онтологічні надбання й теоретичні напрацювання в сфері потенціалу регулюючих інструментів держави підтверджують зростання інституціональної ролі держави в трансформації ринкових моделей розвитку. Обгрунтовано, що модернізаційний процес в національному господарстві має базуватися на якісно іншому господарському механізмі, який сприятиме подоланню технологічного відставання й структурного дисбалансу та дозволить реалізувати сучасний інноваційний тренд зростання з орієнтацією на формування високотехнологічного промислового та переробного виробництва. Констатовано, що модернізаційний процес потребує формування інституціонального базису, який здатний забезпечити інвестиційний попит та інноваційну пропозицію, сформувати безперервний за стадіями інноваційний процес, змінити економічні мотиви і стимули, які продукують базисні інститути. Теоретико-методологічні положення дослідження поглиблюють практичні засади інституціонального забезпечення модернізації національної економіки. The analysis of the theoretical foundations and elements of institutional support for the modernization of the national economy is carried out in the article. The theoretical and methodological basis of the study is a systematic approach to the substantiation of theoretical provisions and tools of institutional regulation of modernization dynamics. It is emphasized that the specific realities of transitional social and economic systems, which are transformed into a more perfect model of development, are the ontological foundation for the implementation of modernization transformations. It was established that the market model of economic development during the period of its economic evolution proved stable advantages and the ability to forecast dynamics, and its potential was determined as a key modernization vector. It is argued that the ontological assets and theoretical developments in the field of the potential of state regulatory instruments confirm the growth of the state's institutional role in the transformation of market models of development. The above, in the ontological context, was implemented in three successive stages of the spread of state influence: the formation of a market of free competition; functioning of the economic model with non-systematic involvement of state regulatory instruments; systemic macroeconomic regulation of economic dynamics. It is substantiated that the modernization process in the national economy should be based on a qualitatively different economic mechanism, which will contribute to overcoming the technological lag and structural imbalance and will allow the implementation of a modern innovative trend of growth with an orientation towards the formation of high-tech industrial and processing production. Taking into account the tasks of the modernization process, the adoption of measures to optimize the basic institutions of the national economy, ensuring the operation and influence of market mechanisms, mobilizing resources and scientific potential to support fundamental research and the implementation of the innovation process is argued. It is argued that the modernization process requires the formation of an institutional basis that is capable of ensuring investment demand and innovation supply, forming a continuous innovation process by stages, and changing the economic motives and incentives produced by the basic institutions. he theoretical and methodological provisions of the study deepen the practical principles of institutional support for the modernization of the national economy.
Theoretical basis of modernization transformations of socio-economic systems
Keywords: модернізація; modernization; інновація; innovation; інформатизація; informatization; розвиток; development; інституціональне забезпечення; institutional support; інститут; institute